Exclusivity in the Name of Inclusivity: Religious Moderation in Indonesia from Utopia to Oxymora - Sukri, Muhammad; Hariyanto, Ishak (Fakultas Hukum Universitas PGRI Palangkaraya, 2024)
Religious moderation is the common hope of mankind in this world; therefore, we must hate violence in any name, be it religion or humanity. We must respect, accept, respect, and uphold human values. This article explores how religious moderation as a utopian idea transformed into an oxymora-filled practice. Oxymora in the sense refers to concepts that seem to be contradictory or opposite to each other but, if examined more deeply, can produce new meanings with nuances of irony and paradox. This oxymoron can be seen in the social, political, and cultural realities in Indonesia by giving birth to the diction of